Exploring the Use of Padlet in Synchronous Learning: Students’ Perceptions of its Advantages and Disadvantages - Fauzul Etfita; Sri Wahyuni; Estika Satriani; Alber Alber; Asnawi Asnawi (Yayasan Visi Intan Permata, 2022)
As a result of the Covid-19 epidemic, educators in Indonesia have had experience dealing with synchronous learning, which has challenged them to select an interesting and engaging method, strategy, or tool to aid the teaching and learning process. Padlet was eventually chosen as the solution to this study. Padlet is a virtual wall that is used to build students' interest in learning English, specifically writing. In this study, the researchers used a descriptive quantitative research design with a sample of 96 students to assess their perceptions of using Padlet as a virtual wall. Numerous factors such as utility, knowledge, engagement, enjoyment, motivation, and ease of use were determined through a questionnaire-based survey which was then distributed as benefits and drawbacks of using Padlet. According to the findings, the students agreed that Padlet provided several benefits to their learning process. On the other hand, students disagreed with Padlet's disadvantages. Therefore, the result implied that the expectation to enhance knowledge is the major factor influencing students’ perceptions of the Padlet utilization in synchronous learning